The annotated Godfather : 50th anniversary edition with the complete screenplay, commentary on every scene, interviews, and little-known facts - Coppola, Francis Ford, 1939-; Puzo, Mario, 1920-1999 (Black Dog & Leventhal Publishers, Hachette Book Group, 2021)
"Celebrating the 50th anniversary of The Godfather, this authorized, annotated and illustrated edition of the complete, unedited screenplay includes all the little-known facts, behind-the-scenes intrigue, and first-person reflections from cast and crew members on the making of this landmark film."--Back cover.